2016
DOI: 10.1186/s13643-016-0323-4
|View full text |Cite
|
Sign up to set email alerts
|

Self-management interventions to improve skin care for pressure ulcer prevention in people with spinal cord injuries: a systematic review protocol

Abstract: BackgroundPressure ulcers are a serious, common, lifelong, and costly secondary complication of spinal cord injury (SCI). Community-dwelling people with a SCI can prevent them with appropriate skin care (i.e. pressure relieving activities, skin checks). Adherence to skin care remains suboptimal however, and self-management interventions that focus on improving this have been designed. Little is known on their content, effectiveness, or theoretical basis. The aim of the proposed systematic review is to synthesi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 54 publications
0
10
0
Order By: Relevance
“…Given these concerns and the pressing need for effective SCI skin care self-management interventions, our program of work aims to examine the existing evidence base on these interventions. A first project consisted in a systematic review to investigate skin care self-management interventions (see published protocol [12]). Results of this systematic review are reported in two publications.…”
Section: Introductionmentioning
confidence: 99%
“…Given these concerns and the pressing need for effective SCI skin care self-management interventions, our program of work aims to examine the existing evidence base on these interventions. A first project consisted in a systematic review to investigate skin care self-management interventions (see published protocol [12]). Results of this systematic review are reported in two publications.…”
Section: Introductionmentioning
confidence: 99%
“…We published a protocol [ 13 ] prior to undertaking this review. Common search and study selection procedures were used to address aims 1 and 2.…”
Section: Methodsmentioning
confidence: 99%
“…A data extraction spreadsheet was designed in Excel to capture general information, study characteristics, participants, intervention characteristics, measurements, data analyses, and intervention effects (see protocol [ 13 ]). It was piloted on two papers reporting SCI behavioral interventions and ineligible for inclusion in this review.…”
Section: Methodsmentioning
confidence: 99%
“…A number of additional systematic reviews have been registered with the Cochrane Wounds Editorial Base, the protocols for which are currently in the process of being developed, or the reviews themselves undertaken [79][80][81][82][83][84][85] ( Table 3). In addition to these, protocols for other (non-Cochrane) systematic reviews have recently been published, which look specifically at interventions for PUs in people with SCI (e.g., self-management interventions to improve skin care for PU prevention [86]).…”
Section: Upcoming Reviewsmentioning
confidence: 99%